2009
DOI: 10.1002/pbc.21975
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of recurrent or refractory acute lymphoblastic leukemia in infants with MLL gene rearrangements: A report from the Japan infant leukemia study group

Abstract: The prognosis of infants with recurrent or refractory MLL-R ALL is extremely poor despite alternative treatments including HSCT; therefore, it is necessary to develop novel treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 22 publications
3
32
0
2
Order By: Relevance
“…Another key conclusion from these studies was the need for more effective postremission therapy, as a high proportion of relapse (61.7%, n =21/34) occurred before HSCT. 39 Age <6 months was the only independent prognostic factor associated with inferior outcome for MLL -rearranged infants (5-year EFS 27.8% <6 months vs 52.9% ⩾6 months) with CNS disease at diagnosis identified on univariate analysis. 37 Compared with the germline group, univariate analysis demonstrated that MLL -rearranged infants were significantly younger, had higher WBC counts, increased frequency of CNS disease and CD10 negativity at diagnosis.…”
Section: The Present: Infant-specific Collaborative Group Protocolsmentioning
confidence: 85%
“…Another key conclusion from these studies was the need for more effective postremission therapy, as a high proportion of relapse (61.7%, n =21/34) occurred before HSCT. 39 Age <6 months was the only independent prognostic factor associated with inferior outcome for MLL -rearranged infants (5-year EFS 27.8% <6 months vs 52.9% ⩾6 months) with CNS disease at diagnosis identified on univariate analysis. 37 Compared with the germline group, univariate analysis demonstrated that MLL -rearranged infants were significantly younger, had higher WBC counts, increased frequency of CNS disease and CD10 negativity at diagnosis.…”
Section: The Present: Infant-specific Collaborative Group Protocolsmentioning
confidence: 85%
“…The low rates of second remission reported by the Japanese Pediatric Leukemia Study Group (JPLSG) in patients relapsing after treatment for infant ALL are consistent with this hypothesis. 21 …”
Section: Characteristics Of Infant Leukemiamentioning
confidence: 99%
“…Hematopoietic stem cell transplantation can be an effective treatment for certain types of malignant diseases involving bone marrow cancer, mainly leukemia, lymphoma, or myeloma [1][2][3][4][5]. For any transplant in which stem cells come from a donor, it is necessary to ensure a close matching of the human leukocyte antigen (HLA) genetic components as their constituent gene products play vital roles in immune response.…”
Section: Introductionmentioning
confidence: 99%